Farm advisory services and knowledge growth in Italy: Comparison among three regional intervention models - Concetta Menna; Ferdinando Gandolfi; Maria Passari; Marcello Cannellini; Giorgio Trentin; Teresa Del Giudice; Carla Cavallo; Imma Cigliano (Italian Review of Agricultural Economics (REA), 2020)
The profound changes in European policy for farms advisory services (FAS) require a period of experimentation and results observation before the new CAP 2021-2027. This paper focuses on Measure 2 of Rural Development Programme (RDP) 2014-2020. The paper is focused on the description of case studies in three Italian regions: Campania, Emilia-Romagna and Veneto. Different Measure 2-sub-measure 2.1 models are analyzed through a qualitative approach, using a conceptual framework adapted by Birner et al. (2009). The paper contributes to the ongoing debate in the scientific literature on the strengths and weakness of policy intervention focused on tailored advisory services to force a broader Agricultural Innovation System.
Keywords: O13; Q16; Q18; 330; knowledge; innovation; European knowledge policy